Pengaruh Financial Technology Dan Akses Permodalan Terhadap Kinerja Umkm Pada UKM Di Kota Sukabumi - Resti Ganis Yuliani; Nor Norisanti; R. Deni Muhammad Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
There is a decrease in the number of sales of MSMEs in Sukabumi City, which is one of the dimensions of MSME performance. This is possible because these MSMEs have not maximized financial technology, namely payment gateaway and are suspected because they do not get sufficient access to capital so that they are unable to produce food with large portions both in terms of the openness of information obtained and its convenience. The purpose of this study was to determine the effect of financial technology and access to capital on the performance of umkm in MSMEs in the city of sukabumi. this research uses quantitative research methods with descriptive and associative approaches. The population used in this study were MSMEs Restaurant in Sukabumi City with a total of 89 MSMEs as samples. The results of this study indicate that there is an influence between financial technology on the performance of MSMEs because the value of t count obtained is greater than t table, namely 2.994> 1.987. And there is an influence between Access to Capital on the performance of MSMEs because the value of t count obtained is greater than the value in the t table, namely 5,149> 1,987. Keywords: Financial Technology, Access To Capital, Performance, MSMEs